1999
DOI: 10.1161/01.atv.19.5.1162
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans Contribution to Association of Lp(a) and LDL With Smooth Muscle Cell Extracellular Matrix

Abstract: Abstract-Lp(a) interference with fibrinolysis could contribute to atherothrombosis. Additionally, accumulation of Lp(a) and LDLs, could lead to cholesterol deposition and foam cell formation in atherogenesis. The interactions between Lp(a) and LDL could cause their entrapment in the extracellular matrix of lesions. We found that association of Lp(a) with matrix secreted by cultured human arterial smooth muscle cells increased 2 to 3 times the subsequent specific binding of radioactive LDL. Chondroitin sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 49 publications
0
20
0
2
Order By: Relevance
“…The fact that apoB, apo(a), and OxPL did not necessarily uniformly colocalize suggests that the apoB and OxPL components of Lp(a) may be degraded and removed but that the apo(a) component continues to be bound to the plaque and have a longer residence time ( 38 ). It also suggests that additional and quantitatively signifi cant amounts of OxPL are formed in the vessel wall in situ and independently of those OxPL potentially carried by Lp(a).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that apoB, apo(a), and OxPL did not necessarily uniformly colocalize suggests that the apoB and OxPL components of Lp(a) may be degraded and removed but that the apo(a) component continues to be bound to the plaque and have a longer residence time ( 38 ). It also suggests that additional and quantitatively signifi cant amounts of OxPL are formed in the vessel wall in situ and independently of those OxPL potentially carried by Lp(a).…”
Section: Discussionmentioning
confidence: 99%
“…CSPGs are also important during cholesterol deposition and foam-cell formation in atherogenesis. 48 The function of EMR2/ CD97 expressing macrophages binding to CS in atherosclerotic lesions would be an interesting area of study. Finally, Decorin, another DS-containing PG, is markedly increased in the tumor stroma of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…54 Although the mechanisms of its atherogenicity are not fully known, the increased retentive properties of the unique apo(a) moiety likely contribute to this effect. 55,56 Whether Lp(a), once retained, is more easily modifiable into more atherogenic forms and/or otherwise is particularly potent at eliciting maladaptive responses represent areas of ongoing investigation. For example, a series of experimental and clinical studies by Tsimikas and colleagues 57,58 have shown that Lp(a) is rich in potentially atherogenic oxidized phospholipids, a property shown to be predictive of atherosclerotic vascular disease in humans.…”
Section: Lipoprotein(a) and Remnant Lipoproteinsmentioning
confidence: 99%